Priodontes maximus (Cingulata: Chlamyphoridae) - Carter, Tracy S. (2016)
Priodontes maximus (Kerr, 1792), called the giant armadillo, is monotypic and by far the largest extant armadillo. Average adult weight is about 30 kg (in captivity, as high as 80 kg). Its carapace extends about halfway down its sides, making it impossible to curl up tightly. It is dark brown to black dorsally, with a broad light band around the lower part of its carapace. It primarily digs to escape, enhanced by its 20-cm, sickle-shaped nail on its 3rd forefingers. P. maximus is widely distributed in South America but nowhere abundant. It is affected by habitat loss and fragmentation, agriculture, hunting, collection for museum specimens, and illegal animal trafficking. P. maximus is listed as "Vulnerable" by the International Union for Conservation of Nature and Natural Resources.